1994
DOI: 10.1177/104345429401100305
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Behavioral, Affective, and Somatic Responses to Pediatric Bone Marrow Transplantation: Development of the BASES Scale

Abstract: A new measure to assess behavioral, affective and somatic outcomes in the acute phase of bone marrow transplant is described. The Behavioral Affective and Somatic Experiences Scale (BASES) is a 38 item nurse-report instrument, with five subscales labeled Somatic distress, Compliance, Mood/Behavior, Interactions, and Activity. A series of pilot studies were conducted to refine the content of the BASES scale and to establish its psychometric properties in terms of internal consistency, inter-rater reliability, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 13 publications
3
45
0
1
Order By: Relevance
“…12 Within the health-related perspective, some researchers have investigated the degree of emotional distress and impairment of normal functioning specific to the treatment of patients' medical illness during the acute stage of hospitalization following the BMT. 4 However, the subtle and sometimes chronic late-effect changes in health-related quality of life of BMT survivors will need to be documented prospectively throughout the recovery period.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Within the health-related perspective, some researchers have investigated the degree of emotional distress and impairment of normal functioning specific to the treatment of patients' medical illness during the acute stage of hospitalization following the BMT. 4 However, the subtle and sometimes chronic late-effect changes in health-related quality of life of BMT survivors will need to be documented prospectively throughout the recovery period.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%
“…3) or may express difficult behavior and negative moods. 4,5 Increased levels of symptoms such as anxiety, depression, anger, and hypervigilence are generally seen as peaking during the period of hospitalization and as reflecting reasonable responses to highly aversive situationally-based stressors (eg daily aversive medical procedures, acute toxicity of chemotherapy, prolonged hospitalization and social isolation). Symptoms of psychological distress have been reported to gradually dissipate over time in many children as they recover and family life regains normality.…”
mentioning
confidence: 99%
“…11 The SCT may place these children at additional risk for poor HRQOL. Children's HRQOL has been reported to be generally poor following the SCT but to improve by 4-6 months post-SCT; 3,4,12,13 and even 12 months post-SCT. 1,3 However, lower physical, emotional and social scores, higher bodily pain, and lower general health and self-esteem scores have been reported in SCT survivors than healthy norms.…”
Section: Introductionmentioning
confidence: 99%
“…A citation review of the reference lists from these articles and other articles found by the authors added one additional paper [46]. In addition, one author we emailed provided an additional citation [47] resulting in a total of 28 articles that discussed the development and psychometric evaluation of 16 disease-specific QOL instruments.…”
Section: Resultsmentioning
confidence: 99%